Electrocardiogram Analysis-Based to Track Fatigue during Commercial Home Construction Tasks - Artanto, Ardi; Ghiffari, Ahmad; Noviyanti, Noviyanti; Utama, Budi; Tia Fhadillah, Rafika; Anisa Suardin, Lucille (Jurnal Ilmiah Kesehatan (JIKA), 2024)
The presence of fatigue among workers in the commercial house construction industry presents substantial obstacles to both the personal welfare of individuals and the overall efficiency of construction projects. The objective of this study is to investigate how individual factors, namely nutritional status, affect degrees of fatigue in this specific occupational group. Data was gathered from 45 construction workers in November 2023 using a cross-sectional methodology. Total sampling approaches were employed, and persons with pre-existing health issues were excluded. Analyzed were the univariate and bivariate data, which uncovered a noteworthy correlation between nutritional status and tiredness level (p-value=0,028). Although there were no significant correlations between age and sleep quality, the results emphasize the significance of dietary determinants in influencing tiredness levels among construction workers. Implications arise from the necessity of implementing specific interventions for example wellness and occupational diet program to encourage adequate nutrition and improve the well-being and productivity of workers in the construction sector. These findings enhance the progress of occupational health research and offer potential applicability for guiding standard of procedure and practical methods to prevent fatigue-related hazards especially in construction environments.